Stability Study of Water Ambulance in East Kalimantan Inland Waterways - Alamsyah; Ardhi Hidayatullah; Wira Setiawan; Suardi; Habibi; Samsu Dlukha Nurcholik; Wardina Suwedy (WAVE: Jurnal Ilmiah Teknologi Maritim, 2023)
This paper discusses the prediction of ship stability before sailing. This study aims to determine the stability value of the water ambulance in specific operating scenarios. The method used in this study is the B-splines mathematical equation and the optimization method using Maxurf software, which varies ship loading by 100% DWT, 50% DWT, and 25% DWT. The results of the study showed that 100% DWT had a maximum GZ value of 40 degrees and an initial GM of 1.240 meters; 50% DWT conditions had a maximum GZ value of 41.8 degrees and an initial GM of 0.711 meters; and 25% DWT conditions had a maximum GZ value of 43.2 degrees and an initial GM of 0.653 meters. The initial GM value increases with an increasing DWT value. Meanwhile, the maximum GZ value decreased as the DWT value increased. All operational scenarios are determined to meet HSC 2000 Annex 8 monohull criteria.